Chondrocytes from osteoarthritic cartilage of obese patients show altered adiponectin receptors expression and response to adiponectin - Harasymowicz, Natalia Sara; Azfer, Asim; Burnett, Richard; Simpson, Hamish; Salter, Donald M. (Journal of orthopaedic research, 2021)
Obesity and osteoarthritis (OA) are well‐known comorbidities and their precise molecular interactions are still unidentified. Adiponectin, a major adipokine, known to have an anti‐inflammatory effect in atherosclerosis or Type 2 Diabetes Mellitus (T2DM), has also been postulated to be pro‐inflammatory in OA. This dual role of adiponectin is still not explained. The precise mechanism by which adiponectin affects cartilage and chondrocytes remains to be elucidated. In the present observational study chondrocytes from 30 patients with OA (18 females and 12 males) undergoing total knee replacement (TKR) were isolated. Expression of adiponectin receptors 1 and 2 (ADIPOR1 and ADIPOR2) was examined both at gene and protein levels in chondrocytes. The difference in adiponectin receptor expression between lean and obese patients with OA and the role of adiponectin in regulating pro‐inflammatory genes (MCP‐1, IL‐6, and VCAM‐1, MMP‐1, MMP‐2, and TIMP‐1) has been investigated. We found that ADIPOR1 represented the most abundant adiponectin receptor in primary OA chondrocytes. ADIPOR1 and ADIPOR2 genes and ADIPOR1 protein were differently expressed in OA chondrocytes obtained from obese compared with lean patients with OA. Adiponectin induced gene expression of MCP‐1, IL‐6, and MMP‐1 in all OA patients’ chondrocytes. In contrast, VCAM‐1 and MMP‐2 were differently regulated by adiponectin depending on the patient's body mass index. This study suggests that adiponectin and ADIPOR1 may have important roles in the pathogenesis of cartilage degeneration in OA of obese subjects.